2019
DOI: 10.20417/nzjecol.43.24
|View full text |Cite
|
Sign up to set email alerts
|

Snacks in the city: the diet of hedgehogs in Auckland urban forest fragments

Abstract: Urbanisation causes fragmentation of natural habitats, which results in loss of biodiversity, while promoting an environment that can facilitate invasive species. However, forest fragments are an important refuge for native species and therefore understanding and mitigating threats in fragments is critical. While the impacts of some mammalian pest species, such as rats (Rattus spp.), are relatively well-known in New Zealand, hedgehogs (Erinaceus europaeus) are relatively understudied invasive mammals, and thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…This may include research on many endangered farmland species such as Eurasian skylarks (Alauda arvensis), grey partridges (Perdix perdix), Northern lapwings (Vanellus vanellus) or European hamsters (Cricetus cricetus), but also, on species outside the farmland context such as for example sand cats (Felis margarita) in the desert, bird nests on cliffs, or hedgehogs (Erinaceus roumanicus) in the park. Another field of application is the detection and elimination of invasive species 17,3738 . thermal imaging: general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may include research on many endangered farmland species such as Eurasian skylarks (Alauda arvensis), grey partridges (Perdix perdix), Northern lapwings (Vanellus vanellus) or European hamsters (Cricetus cricetus), but also, on species outside the farmland context such as for example sand cats (Felis margarita) in the desert, bird nests on cliffs, or hedgehogs (Erinaceus roumanicus) in the park. Another field of application is the detection and elimination of invasive species 17,3738 . thermal imaging: general.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal imaging techniques to study wildlife were first tested in the late 1960's on white-tailed deer, Odocoileus virginianus 13 , and have afterwards been used to detect, survey or observe a range of different mammals, birds and invertebrates 12 . To date, the smallest mammals that have been systematically studied using thermal imaging are ungulate fawns, adult hares (Lepus europaeus), adult rabbits (Oryctolagus cuniculus) and hedgehogs (Erinaceus europaeus) [14][15][16][17] . However, some studies have reported a rather low detection rate, stressing the fact that alternative approaches are needed 15,18 .…”
Section: Detecting Small and Cryptic Animals By Combining Thermographmentioning
confidence: 99%
“…Finally, Morris (1988) also mentions success in finding hedgehogs with a dog although this is not described in detail. IRT cameras have been used successfully in Regent's Park, London, UK (Bowen et al 2019) and forest fragments in Auckland, New Zealand (Nottingham et al 2019). Conversely, Haigh et al (2012) concluded that the IRT camera that they used was ineffective.…”
Section: Introductionmentioning
confidence: 99%
“…Hedgehog behaviour and dietary preferences would suggest that increases in beetle could be a significant driver of increased hedgehog tracking. Unlike rats and mice which are generalist omnivores, hedgehogs are primarily insectivorous with invertebrates making up the bulk of hedgehog diets (Hendra, 1999;Nottingham et al, 2019). Beetles in particular have been found…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other introduced mammals which show greater omnivory and rely more heavily on fruits and vegetation for food, hedgehogs primarily feed on invertebrates which can account for around half of the relative volume of hedgehog stomach contents (Nottingham et al, 2019).…”
Section: Hedgehogsmentioning
confidence: 99%